Analisis Reaksi Emiten Yang Terdaftar Di Bursa Efek Indonesia Terhadap Dampak Covid-19 - Nababan, Alwi Ihsan; Irawati, Nisrul; Muluk, Chairul (Politeknik Ganesha Medan, 2024)
The purpose of this study was to find out and analyze differences in Abnormal Return & Trading Volume Activity before and after the announcement of the first case of Covid-19 in Indonesia, Micro-Scale Lockdown and Emergency Lockdown in companies listed on the Indonesia Stock Exchange for the 2020-2021 period. The type of research used is case study research (Event Study). The samples were 48 companies listed in Healthcare, Technology, Transportation & Logistics sectors listed on the Indonesia Stock Exchange for the period 2020-2021, taken by using a purposive sampling technique. The analysis technique used is the Wilcoxon Signed Rank Test. The results showed there was no significant difference in abnormal returns on the announcement of the first case of Covid-19 in Indonesia, Micro-Scale PPKM, and Emergency PPKM in the Healthcare, Technology, Transportation & Logistics sector. There is a significant difference in Trading Volume Activity on the announcement of the first case of Covid-19 in Indonesia, Micro-Scale PPKM but there is no significant difference in Trading Volume Activity before and after Emergency PPKM in the Healthcare sector. There is a significant difference in Trading Volume Activity on Micro-Scale PPKM but there is no significant difference in Trading Volume Activity before and after the announcement of the first case of Covid-19 in Indonesia and Emergency PPKM in the Technology sector. There is no significant difference in Trading Volume Activity on the announcement of the first case of Covid-19 in Indonesia, Micro-Scale PPKM, and Emergency PPKM in the Transportation & Logistics sector.